Analysis of the Influence of Profitability, Company Size, and Business Risk on Capital Structure (A Study of Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2018-2022 Period) - Ana Amalia Harnawan; Eskasari Putri (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of profitability, company size, and business risk on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange for the 2018–2022 period. The study uses a quantitative approach with a multiple linear regression design. The population consists of food and beverage companies active on the IDX during that period. A sample of 17 companies was selected through a purposive sampling technique with the criteria of the company remaining listed, consistently publishing financial reports, not experiencing losses, and having complete data, resulting in 85 observations (17 companies × 5 years). Secondary data were obtained from financial reports on the official IDX website (www.idx.co.id) and company websites. The analysis includes descriptive statistics, classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation), and hypothesis testing (t-test, F-test, and coefficient of determination R²). The results show that companies with high profitability tend to be more flexible in managing their capital structure, while large companies rely more on internal funding, reducing their dependence on debt. Business risk is not a major determining factor in the food and beverage sector, which has stable demand. Consequently, company management can prioritize increasing profitability and managing company size to achieve an optimal capital structure, while operational risk can be managed through a product diversification strategy. Future research is recommended to add variables such as liquidity or asset structure and expand to other sectors for broader generalization.